Rinsing with L-Ascorbic Acid Exhibits Concentration-Dependent Effects on Human Gingival Fibroblast In Vitro Wound Healing Behavior - Tatcha Chaitrakoonthong; Ruchanee Ampornaramveth; Paksinee Kamolratanakul (International Journal of Dentistry)
Vitamin C or L-ascorbic acid has diverse functions in the body, especially healing promotion in tissue injury via participating in the hydroxylation reactions required for collagen formation. Systemic administration of vitamin C plays an important role on gingival fibroblast proliferation and functions. Whether local or rinsing administration of vitamin C alters gingival fibroblast wound healing behavior remains unclear. The aim of this study was to investigate the rinsing effect of vitamin C on gingival fibroblast behavior utilizing an in vitro wound healing model. Primary human gingival fibroblasts isolated from gingival tissue were rinsed with medium containing various concentrations of vitamin C. The rinsing effect of vitamin C on in vitro wound healing was assessed using a scratch test assay. Cell migration, cell viability, and extracellular matrix gene expression were analyzed by transwell migration assay, MTT assay, and real-time RT-PCR, respectively. We found that rinsing with 10 or 20 µg/ml vitamin C significantly increased fibroblast migration (p≤0.05). However, no significant effect was found in the cell viability or in vitro wound healing assays. In contrast, rinsing with 50 µg/ml vitamin C significantly delayed wound closure (p≤0.05). Real-time PCR demonstrated that 50 µg/ml vitamin C significantly increased fibroblast expression of COL1, FN, IL-6, and bFGF. The data demonstrate that rinsing with vitamin C (10/20 µg/ml) accelerates fibroblast migration. However, 50 µg/ml of vitamin C increases the expression of COL1, FN, IL-6, and bFGF, which are related to fibroblast wound healing activity. Prescribing vitamin C with the appropriate duration and drug administration method should be determined to maximize its benefit.